017 Neurology virtual clinic: quality improvement project. Issue 9 (12th August 2022) - Ashjaei, Shayan; Varmpompiti, Kyriakoula; Alexandratou, Anna; Wu, Kit; Stanton, Biba; Theochari, Evangelia; Weeks, Robert
Abstract : Background: Neurology patients with complex diagnoses in a busy tertiary centre can undergo multiple investigations to reach a diagnosis and are usually discharged with pending results, as tests can take a considerable amount of time to be processed (and released). Aim: We set up a Virtual Clinic to follow-up patients' results post discharge to avoid loss to follow up and improve safety of patient care. Methods: We identified a significant proportion of neurology inpatients who were not followed-up efficiently (30.8% over 3-month-period) and addressed this issue by initiating a Virtual Clinic. The clinic was run weekly by neurology junior doctors, with protected clinic hours. The outcome of the clinic was communicated to the referring neurology consultant. We compared the follow up rates in the three months pre-clinic (October to December 2019) to the three months after setting up the clinic (January to March 2020). Results: Using the PDSA methodology, we successfully managed to increase the follow-up for outstanding investigations to 68.8% from 30.8% (pre-clinic setup), via the implementation of the Neurology Virtual Clinic. We re-audited for another three-month period using the same methodology. For the period September to November 2020, this percentage increased further to 73.68%. Conclusion: This new service was effective at improving test result monitoring and decreased the number of investigations that were not followed up promptly. Most importantly improved the safety of our patients' care.